The Empowerment of Menopausal Women for Preparation Toward Active Aging Society - Pangsiri, Mujjalin (Community and Social Development Journal, 2021)
This research aim to study the empowerment of menopausal women for preparation toward active aging society withParticipatory Action Research (PAR) and compared the learning process before and after self-empowerment. The sample consisted of 100 menopausal women age 40-59 years, Sanpatong district Chiangmai province . The data collected by questionnaires ,group discussion by empowerment. Data were analyzed using descriptive statistics, multiple regression analysis (MRA:Stepwise), content analysis and comparison of the empowerment results before and after activities by paired t-test statistics. The research results were found that the average age of women was 45.70 years. Most of them had marital and do not have any underlying disease. Overall symptoms of changes in estrogen deficiency in menopausal women were low level. When analyzing the behavior of preparing for the elderly among menopausal women. The overall were at a moderate level. Especially in the social and environmental aspects. In addition, it was found that psychological preparation, physical preparation, cognitive preparation and expectations for self-care, mental preparation, social and environmental preparation , knowledge and positive attitudes towards being an elderly person and experience in caring for the elderly could jointly predict changes in preparation 59.30 %. The Empowerment of menopausal women for a quality aging society and for those who are entering the elderly, it was found that the physical and mental preparation needed to be focused on preparing for the elderly in the future. With emphasis on promoting holistic health in all aspects of health by comparing the power of health promotion of menopausal women before and after the activity found that the organization of exercise activities and changes in hormonal deficiency. The mean post-event was significantly higher than before the activity at 0.05 level.